500=((x-(0.21x))0.25)-0.1

Simple and best practice solution for 500=((x-(0.21x))0.25)-0.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 500=((x-(0.21x))0.25)-0.1 equation:


Simplifying
500 = ((x + -1(0.21x)) * 0.25) + -0.1

Remove parenthesis around (0.21x)
500 = ((x + -1 * 0.21x) * 0.25) + -0.1

Multiply -1 * 0.21
500 = ((x + -0.21x) * 0.25) + -0.1

Combine like terms: x + -0.21x = 0.79x
500 = ((0.79x) * 0.25) + -0.1

Remove parenthesis around (0.79x)
500 = (0.79x * 0.25) + -0.1

Reorder the terms for easier multiplication:
500 = (0.79 * 0.25x) + -0.1

Multiply 0.79 * 0.25
500 = (0.1975x) + -0.1

Reorder the terms:
500 = -0.1 + (0.1975x)

Solving
500 = -0.1 + (0.1975x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(-0.1975x)' to each side of the equation.
500 + (-0.1975x) = -0.1 + (0.1975x) + (-0.1975x)

Combine like terms: (0.1975x) + (-0.1975x) = 0.0000
500 + (-0.1975x) = -0.1 + 0.0000
500 + (-0.1975x) = -0.1

Add '-500' to each side of the equation.
500 + -500 + (-0.1975x) = -0.1 + -500

Combine like terms: 500 + -500 = 0
0 + (-0.1975x) = -0.1 + -500
(-0.1975x) = -0.1 + -500

Combine like terms: -0.1 + -500 = -500.1
(-0.1975x) = -500.1

Divide each side by '-0.1975'.
x = 2532.151899

Simplifying
x = 2532.151899

See similar equations:

| 44x^2-39x+9=0 | | 39x^2-31x+6=0 | | (4b^2-4b)=0 | | 500=(x-(0.21x))0.25 | | (9b^2-81)=0 | | 4x-2(12x-x)=18 | | y^2-2x-6y+13=0 | | Sin(6x)*cos(6x)+1=0 | | Sin(6x)*cos(6x)-1=0 | | 8x-32=128-2x | | 8x-32=128+2x | | 8x-2x=128-32 | | 10x-x-2=-7 | | 10x-x-2=-7 | | T+10=11 | | 2w+2w-2+2w-2=68 | | 96=72 | | 3(4*3)+8= | | 10x-2=90 | | 9*7+4*4= | | 3x+17=73+5x | | 4x-3=-24 | | 98=-10 | | 28x+2= | | 4(-x+5)=2(x+7)-6x | | 5x-4=-3x+12-2x | | 3x+6=6x+9-7x | | -5a+7+4a=-(a+7) | | F(x)=2(x^2-9x+5)-5(x-k) | | n+40=41 | | -5a-7+4a=-(a+7) | | 6x-5=x^2+4 |

Equations solver categories